Climate change in Longyearbyen, Svalbard: Observed societal impacts and adaptations ... - Meyer, Alexandra (Zenodo, 2021)
Abstract Longyearbyen, Svalbard, has become somewhat of a showcase of Arctic climate change, however, we know little about the societal impacts of and local responses to these changes. Drawing on ethnographic fieldwork and qualitative interviews with planners, engineers, architects, scientists, people working in construction, and local politicians in Longyearbyen, and focusing on climate change impacts on the built environment, this paper aims to 1) describe observed changes and perceived societal impacts of climate change, and 2) describe and discuss adaptation measures, related discourses on adaptation, as well as challenges to adaptation. This paper aims to fill a gap by examining climate change impacts and adaptation in a non-indigenous “community of experts”, in a Western sense of the term. Those involved in planning, building and maintaining Longyearbyen observe environmental changes and various impacts on the built environment of the town. From their point of view, climate change is considered a ...